Divina Iura Episcoporum: Studi sulla teologia dell'episcopato del Vaticano I alla vigilia del Vaticano II - Bua, Pasquale (Lateranum, 2021)
The article examines three works on First Vatican Council's theology of the episcopate, written by Gustave Thils, Jean-Pierre Torrell and Georges Dejaifve. These essays, all published in 1961, demonstrate how on the eve of Vatican II the attempt to foster a new hermeneutical approach to Pastor aeternus was feverish in French-speaking Europe (France and Belgium). Using the acts of the Council (preparatory schemes, interventions by the fathers and official reports of the Deputation of the Faith), the authors study the "text" of the constitution in the "context" of the conciliar debates, showing that the ecclesiology of the Vatican I, despite its imbalance on the papacy, recognizes and defends the divina iura episcoporum in its own way.